THE EFFECTIVENESS OF FUN ADVENTURE GAME MEDIA TO INCREASE THE COGNITIVE LEARNING OUTCOMES OF THE STUDENTS ON THE FUNGI MATERIAL FOR GRADE X OF SENIOR HIGH SCHOOL - Aoda Rusdanillah; Isnawati Isnawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Fun Adventure game media is one of the learning media containing a set of board game with questions cards related to Fungi material. The game designed as students adventured in the kingdom of fungi, hence that the learning activities can be more fun and meaningful. This research was aimed to describe the effectivity of fun adventure game media to increase the cognitive learning outcomes of the students on the fungi material for grade X of senior high school. This Fun Adventure game media had been developed based on the ASSURE method (Analyze Learner, State Objectives, Select Media and Materials, Utilize Media and Materials, Require Learner Performance and Evaluate and Revise). The effectiveness trial of the valid media was conducted on 15 students of grade X MIA 2 SMAN 1 Sidayu Gresik in March 2018. The effectiveness of the Fun Adventure game media in terms of learning outcomes of students with value of gain score was 0.73 (category highly increasing) with the overall indicator completed, and in terms of student responses with the percentage of 97.78% of students gave positive respons to the Fun Adventure game media. Based on these data, it can be concluded that Fun Adventure game media was effective to increase the cognitive learning outcomes of students. Key words: effectiveness, Fun Adventure game media, cognitive learning outcomes, fungi material.